Carbon Quantum Dots Based on Marine Polysaccharides: Types, Synthesis, and Applications - Torres, F.G.; Gonzales, K.N.; Troncoso, O.P.; Cañedo, V.S. (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The marine environment offers a vast array of resources, including plants, animals, and microorganisms, that can be utilized to extract polysaccharides such as alginate, carrageenan, chitin, chitosan, agarose, ulvan, porphyra, and many more. These polysaccharides found in marine environments can serve as carbon-rich precursors for synthesizing carbon quantum dots (CQDs). Marine polysaccharides have a distinct advantage over other CQD precursors because they contain multiple heteroatoms, including nitrogen (N), sulfur (S), and oxygen (O). The surface of CQDs can be naturally doped, reducing the need for excessive use of chemical reagents and promoting green methods. The present review highlights the processing methods used to synthesize CQDs from marine polysaccharide precursors. These can be classified according to their biological origin as being derived from algae, crustaceans, or fish. CQDs can be synthesized to exhibit exceptional optical properties, including high fluorescence emission, absorbance, quenching, and quantum yield. CQDs’ structural, morphological, and optical properties can be adjusted by utilizing multi-heteroatom precursors. Moreover, owing to their biocompatibility and low toxicity, CQDs obtained from marine polysaccharides have potential applications in various fields, including biomedicine (e.g., drug delivery, bioimaging, and biosensing), photocatalysis, water quality monitoring, and the food industry. Using marine polysaccharides to produce carbon quantum dots (CQDs) enables the transformation of renewable sources into a cutting-edge technological product. This review can provide fundamental insights for the development of novel nanomaterials derived from natural marine sources.
Keywords: Polysaccharide; Nanotechnology; Nanomaterials; Carbon fibers; Materials science; Biocompatibility; Chemistry; Organic chemistry; Composite number; https://purl.org/pe-repo/ocde/ford#1.04.04